Analysis of Differentiated Learning Strategies on Student Learning Outcomes - Puteri, Fadhilah Nur Ramadhani Rizqiyah; Alfiansyah, Iqnatia (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
History shows that the Indonesian nation has been independent for 77 years, the education of students in this country has become an important icon in people's lives who need direction towards a better future. Long enough time has passed, it is only natural that this country will learn valuable lessons to make history for a better future. The subjects in this study were class V teachers to analyze the differentiated learning strategies carried out by the teacher during the learning process in class. This qualitative research emphasizes more on descriptive reports that aim to describe or describe existing phenomena, both scientific and man-made phenomena. In other words, this learning model will give students the flexibility to increase their potential according to their readiness to learn, their interests, and their learning profile. Effect of Using Differentiation Learning allows teachers to meet the needs and expectations of students, this indirectly increases the creativity of students.